2010
DOI: 10.1088/0952-4746/30/2/s03
|View full text |Cite
|
Sign up to set email alerts
|

Background dose-rates to reference animals and plants arising from exposure to naturally occurring radionuclides in aquatic environments

Abstract: In order to put dose-rates derived in environmental impact assessments into context, the International Commission on Radiological Protection (ICRP) has recommended the structuring of effects data according to background exposure levels. The ICRP has also recommended a suite of reference animals and plants (RAPs), including seven aquatic organisms, for use within their developing framework. In light of these propositions, the objective of this work was to collate information on activity concentrations of natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 59 publications
(50 reference statements)
4
14
0
Order By: Relevance
“…Only approximately 1.4 % of the total dose rate is estimated to have come from the FDNPP releases. The total dose rate for squid is 0.15 µGy h −1 from radionuclides measured in this study, and increases to approximately 0.61 µGy h −1 when adding Po-210, a natural radionuclide significant dose contributor in marine organisms (assumes 0.001 Bq L −1 in seawater and a generic marine value of 15 Bq kg −1 whole-body fresh mass, which is consistent with a general value in Hosseini et al, 2010, and with the lognormal 95th percentile of limited squid Po-210 data; Carvalho, 2011;Heyraud et al, 1994;Waska et al, 2008). When median squid data are used (3 Bq kg −1 whole-body fresh mass), the total dose rate is 0.25 µGy h −1 .…”
Section: Dose Rates For Squidsupporting
confidence: 86%
See 2 more Smart Citations
“…Only approximately 1.4 % of the total dose rate is estimated to have come from the FDNPP releases. The total dose rate for squid is 0.15 µGy h −1 from radionuclides measured in this study, and increases to approximately 0.61 µGy h −1 when adding Po-210, a natural radionuclide significant dose contributor in marine organisms (assumes 0.001 Bq L −1 in seawater and a generic marine value of 15 Bq kg −1 whole-body fresh mass, which is consistent with a general value in Hosseini et al, 2010, and with the lognormal 95th percentile of limited squid Po-210 data; Carvalho, 2011;Heyraud et al, 1994;Waska et al, 2008). When median squid data are used (3 Bq kg −1 whole-body fresh mass), the total dose rate is 0.25 µGy h −1 .…”
Section: Dose Rates For Squidsupporting
confidence: 86%
“…As most dose rates to human consumers of seafood typically come from the natural radionuclide Po-210 (∼ 89 %; Johansen et al, 2015), the seafood ingestion dose rates here were compared with and without Po-210 to provide a context of the relative influence of the FDNPP accident radionuclides. For this comparison, a generic Po-210 seafood value of 15 Bq kg −1 was used based on Hosseini et al (2010) and consistent with the conservative (lognormal 95th percentile) based on the limited squid data in Carvalho (2011), Heyraud et al (1994), and Waska et al (2008).…”
Section: Dose From Ingesting Squidmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of these propositions, information on activity concentrations of naturally occurring primordial radionuclides for marine and freshwater ecosystems have been applied and appropriate dosimetry models used to derive absorbed dose-rates for Reference Animals and Plants [18]. Although coverage of activity concentration data is comprehensive for sediment and water, few, or in some cases no, data were found for some organism groups, for most radionuclides.…”
Section: Background Dose Rate Characterisationmentioning
confidence: 99%
“…A literature review conducted by Hosseini et al . (5) revealed that the mean activity concentrations of natural occurring radionuclides in generic marine fish are 83 Bq kg −1 of 40 K, followed by 30 Bq kg −1 of 210 Po, 19 Bq kg −1 of 14 C and 1.8 Bq kg −1 of 228 Ra. Potassium is ingested in many foods that we eat and is a critically important element for proper functioning of the human body.…”
mentioning
confidence: 99%